Lung Cancer with Epidermal Growth Factor Receptor Exon 20 Mutations Is Associated with Poor Gefitinib Treatment Response - Wu, Jenn-Yu; Wu, Shang-Gin; Yang, Chih-Hsin; Gow, Chien-Hung; Chang, Yih-Leong; Yu, Chong-Jen; Shih, Jin-Yuan; Yang, Pan-Chyr (Clinical cancer research, 2008)
Purpose: Clinical reports about responsiveness to gefitinib treatment in patients of non-small cell lung cancer (NSCLC) with mutations in exon 20 of epidermal growth factor receptor (EGFR) are limited. To increase understanding of the influence of exon 20 mutations on NSCLC treatment with gefitinib, we investigated the clinical features of lung cancer in patients with exon 20 mutations and analyzed the gefitinib treatment response. Experimental Design: We surveyed the clinical data and mutational studies of NSCLC patients with EGFR exon 20 mutations in the National Taiwan University Hospital and reviewed the literature reports about EGFR exon 20 mutations and the gefitinib treatment response. Results: Twenty-three patients with mutations in exon 20 were identified. Nine (39%) had coexisting mutations in EGFR exons other than exon 20. Sixteen patients received gefitinib treatment, and a response was noted in 4 patients. The gefitinib response rate of NSCLC with exon 20 mutations was 25%, far lower than those with deletions in exon 19 and L858R mutations. Interestingly, different exon 20 mutations and coexisting mutations seemed to have a different influence on gefitinib response. Conclusions: EGFR exon 20 mutations of NSCLC patients result in poorer responsiveness to gefitinib treatment, but variability exists between different individuals.